Estrasburgo y la detención de inmigrantes: ¿nueva línea jurisprudencial? - Claro Quintáns, Irene (2022)
This article begins with the mention to the concept of “crimmigration”. This notion describes the increasing relationship between migration law and criminal law. The governmental authorities consider that detention can be a useful tool to control the irregular entry and stay in their countries. Moreover, International Human Rights Law allows the detention of migrant to prevent unauthorized entry or to effect deportation. However, from the European perspective, the European Convention on Human Rights has established two limits to the detention: the right to liberty (article 5) and the prohibition of torture or to inhuman or degrading treatment or punishment (article 3). This article provides an overview of the jurisprudence of the European Court of Human Rights regarding both articles, taking into consideration the situation of migrant children in particular.